Development of an Islamic Values-Based Quality Assurance Model for Strengthening Quality Culture in Pesantren: A Bibliometric and Conceptual Approach - Tri Aji Pamungkas; Selvia Ruyatus Saefullah; Mohamad Heri Hadian; Erry Hendriawan; Neni Utami Adiningsih (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Strengthening a culture of quality remains a major challenge in the management of Islamic boarding schools (pesantren) amid increasing demands for accountability, competitiveness, and compliance with educational quality standards. Existing quality assurance models have generally adopted conventional approaches and have not fully integrated Islamic values as the foundation of institutional governance. This study aims to develop an Islamic values-based quality assurance model for strengthening the quality culture in pesantren through a literature review supported by bibliometric analysis. This study employed a qualitative literature review design combined with bibliometric analysis. A total of 236 publications were initially identified from the Scopus database, of which 203 journal articles met the screening criteria and were analyzed using VOSviewer version 1.6.20 to map publication trends, author collaboration, keyword co-occurrence, and emerging research themes related to quality assurance, quality culture, Islamic values, and pesantren. The findings reveal that research on quality assurance and quality culture has grown substantially over the past decade. However, studies integrating Islamic values into quality assurance models for pesantren remain limited and fragmented. Based on these findings, this study proposes a conceptual quality assurance model that integrates the principles of amanah, ihsan, itqan, shura, istiqamah, and continuous quality improvement throughout the quality assurance cycle. The proposed model contributes theoretically by extending the quality assurance discourse through the integration of Islamic values and offers a contextual framework for strengthening sustainable quality culture in Islamic boarding schools. The model is expected to serve as a strategic reference for pesantren administrators, policymakers, and future researchers in developing quality assurance systems that are value-based, sustainable, and globally competitive.